Widen the language development in infants and toddelers - Dwi Nurcahyati; Sukmawati Lopo; Sahara Nur Fadila (Universitas Muhammadiyah Surabaya, 2020)
Abstract,In the initial stages, speech development is a sensorimotor process thatoccurs as a result of the child's interaction with parents. The left hemisphere of thebrain begins to take part in functional roles as soon as speech becomes a symbol. The development of children's communication actually begins early, when he cries. After the age of 3 years children start dialogue longer and ask abstract things. Most couples communicating children are adults, usually parents. A child's speech ability is influenced by several factors, including the ability to hear, physical development of the mouth, and throat and heredity, history of the mother's womb, childbirth, stages of development of the child, environment, hearing loss, intelligence (cognitive), psychological emotions . Children can express their thoughts through language so that others can capture what is thought by children. Children who talk a lot sometimes become a reflection of an intelligent child. Language development for early childhood aims to enable children to communicate verbally with the surrounding environment. The impact of parenting and the environment are the main causes of children's language development not in accordance with the development of language at their age.Keywords: Language development in infants and toddlers